Temperature Dynamic Characteristics Analysis and Thermal Load Dissipation Assessment for Airliner Hydraulic System in a Full Flight Mission Profile - Dong Li; Sujun Dong; Jun Wang; Yunhua Li (Machines, 2022)
This paper deals with the modeling of the thermal load and the simulation of thermal dynamic characteristics for the hydraulic system of a large airliner in a full mission profile. Firstly, the formation mechanism of the thermal load in the hydraulic system is analyzed, and thermal dynamic modeling is conducted of the hydraulic components of an hydraulic system with an immersed heat exchanger employing the lumped parameter thermal node method and oil temperature and power loss of each key node within the hydraulic system within a full mission profile. Then, a thermal dynamic simulation model based on MATLAB/Simulink is established, and the temperatures at the nodes of different components and the absorptive capacity of the fuel heat sink in the thermal management module are calculated. The simulation results show that the thermal management scheme of the heat exchanger, located in the return oil pipeline of the hydraulic piston pump housing and immersed in the central fuel tank, can dissipate the thermal load of the system. This work is of important significance for temperature analysis and thermal load dissipation of the airliner hydraulic system.